Kondisi Sosial Budaya Terkait Pendidikan Anak Pada Masyarakat Petani di Desa Suro Jawa Tengah - Gita Dias Riyana; Oktaviani Adhi Suciptaningsih (Universitas Maritim AMNI Semarang, 2023)
The purpose of this study was to determine the socio-cultural conditions of the farming community in relation to children's education and the socio-economic conditions of the farming community in the village of Suro, Central Java. The method used in this research is descriptive qualitative method. The data collection tools used in this study were observation and interviews. The results of the study show that factors such as limited access to education, traditional belief in the local education system, and the lack of public awareness regarding the importance of formal education are challenges in improving the education of children in Suro Village. However, through joint efforts from the government, community and non-governmental organizations, such as increasing access to formal education, the role of parents in providing support and motivation, campaigns and outreach programs regarding the importance of formal education, can improve the education of children in Suro Village. It is hoped that these efforts can gain strong support from all parties to create a conducive educational environment for the children of Suro Village to prepare for their future. It is hoped that this article can provide an overview of the condition of children's education in farming communities in rural areas and become a reference for the development of sustainable education policies in Indonesia.